A cell-centered finite volume scheme for the diffusive–viscous wave equation on general polygonal meshes. (November 2022) - Wang, Wenhui; Yan, Wenjing; Yang, Di
Abstract: Seismic wave equations based on numerical simulation have become effective tools in geological exploration. Considering the frequency dependence of reflections and fluid saturation in porous mediums, the diffusive–viscous wave theory is necessary to study. In this paper, a cell-centered finite volume scheme for the diffusive–viscous wave equation is proposed on general distorted polygonal meshes. Numerical experiments are provided to demonstrate the convergence rate of the errors in the discrete L 2 norm and interpret the effectiveness by a simulation of the actual geological exploration point.